Moderating Role of Emotional Intelligence in the Relationship Between Despotic Leadership and Psychological Well-Being of Faculty Members in Pakistani Universities - Rizvi, Riffat Abbas (2025)
The study investigates the impact of despotic leadership on the psychological well being (PWB) of faculty members in Higher Education Commission (HEC) recognized public and private sector universities in Pakistan. The research uses a parallel mediation model to examine job stress and cognitive distraction as mediators between despotic leadership and employee wellbeing. Emotional intelligence is examined as moderating amongst the influence of despotic leadership and other mediators, leading to psychological well-being. Data was collected from (N=419) faculty members across various universities and analyzed using SPSS and SMART PLS. The results indicated despotic leadership's significant direct and indirect effects through mediation cognitive distraction and job stress on psychological well-being, moderated by emotional intelligence. This study highlights the need for university-level administrations to consider emotional intelligence and leadership styles in their policies to mitigate job stress and cognitive distractions, thereby enhancing faculty well-being. Future research should explore other leadership styles and additional mediators in academic settings.